Baton, water cannon, teargas: public order partnership (Academic Journal of Internal Affairs, 2018)
The author provides an overview of the various civil strategies and public order responses in the field of public demonstrations since 1968 in Hungary.
Keywords: public order; demonstrations; Hungary